Етапи формування об’ємно-просторової структури церкви Різдва Христового у Тернополі - Дячок, Оксана; Diachok, Oksana (Видавництво Львівської політехніки, 2021)
Наукове дослідження присвячене історичним етапам розвитку одного із найдавніших храмів Тернополя – церкви Різдва Христового, збудованої на початку XVII ст. Складні суспільно-політичні процеси на території Тернопільського краю, конфесійні трансформації змінювали архітектурний образ святині. Церкві вдалось вистояти попри війни, коли була зруйнована майже уся історична частина міста. Наводяться дані про поетапну зміну об’ємно-планувальної структура церкви, яка розпочалась ще у період Реформації, активізацією національно-культурного відродження, організацією при церкві православного братства та зі зміною конфесійної приналежності. Радянський період був найбільш руйнівний для церкви. Наводяться дані про дослідження під час реставраційних розвідок, в ході яких були підтверджені дані, що церква-твердиня входила до загальної оборонної системи Тернополя і гіпотезу дослідників про те, що частина храму була складовою Кам’янецької в’їздової брами міста.

Scientific research is devoted to the historical stages of development of one of the oldest churches in Ternopil – the Church of the Nativity of Christ, built in the early XVII century, which is one of the best examples of Podillya sacred architecture. The church is included in the state register of the national cultural heritage of Ukraine. Complicated socio-political processes in the Ternopil region and confessional transformations changed the architectural image of the shrine. The church managed to survive despite the war when almost the entire historic part of the city was destroyed. The Soviet occupation caused the greatest damage to the sacred complex. The indifference of the authorities to the architectural monument in the modern period and the emergency around the monument almost led to the destruction of the shrine. There is data on the gradual change in the volume and planning structure of the church, which began during the Reformation. The changes were also related to the intensification of national and cultural revival and the organization of the Orthodox Brotherhood at the church. The reconstructions in 1700 were associated with a change of denomination and the conversion of the parish to the Greek Catholic faith. The modernization of the church took place in 1808 to give the cathedral features and the traditional scheme of the Ukrainian three-story church: an additional volume was added to the western facade and the church was crowned with two more decorative heads. As a result of a reconstruction in 1936–1937, the church acquired a modern look. The Soviet period was the most destructive for the church, the church was first transferred to the Russian Orthodox Church, later closed. In 1958, during the expansion of the central street of the city, the bell tower and the fence were demolished. Restoration work began with Ukraine's independence. The article provides data on research during restoration surveys, which confirmed the fact that the church fortress was part of the general defence system of Ternopil and the hypothesis of researchers that part of the temple was part of the Kamyanets entrance gate of the city
Stages of formation of the volume and spatial structure of the church of the nativity of christ in Ternopil
Keywords: defensive temples; church architecture; three-dimensional solution; 726 (477.84)